GMAW Parameters Effects On Microstructural And Mechanical Properties Of TOW SS304 And BS1387 - Mohd Noh, Mohd Zakaria (UTeM, 2016)
Tailored orbital welding is a joining process of tubular product with dissimilar material and size depending on the application environment. One of the most common industries that apply this process is in power plant boiler water piping system. Dissimilar material is used to transmit water at various temperature, either in extremely high temperature water or room temperature water. In order to reduce cost and dependence on high-skill welder, tailored orbital welding of dissimilar material of Stainless Steel (SS) 304 and British Steel (BS) 1387 were performed by Gas Metal Arc Welding (GMAW) with automated fixed nozzle-rotational jig. The fixed nozzle-rotational jig was used to provide “steady hand” and constant travel speed for welding process. Thus, it will increase productivity and repeatability of the process, reducing the weld defects and produce good quality weldment. The study was focused on GMAW parameters variation effects on microstructure formation and mechanical properties of SS304 and BS1387 dissimilar material tailored orbital welding. The weldment quality was tested by performing non-destructive test and weld bead properties was studied to verify the influence of welding parameters variations. The study on microstructure formation, micro hardness and tensile strength were conducted to relate the solidification formation and mechanical properties. In addition, thermal effect was studied to understand the microstructure and micro hardness variations of tailored orbital welding. In this study, Design of Experiment (DOE) was employed to generate process parameter using Response Surface Methodology (RSM) method. Welding parameters include arc current, arc voltage and travel speed as input response, whilst, mechanical properties include micro hardness and tensile strength as output response. The effects of welding parameters on mechanical properties were also studied. Results from non-destructive test show no major defect was occurred. The weld bead dimension studies showed variation in welding parameters affect the weld bead formation. The heat generated during welding process also affect the microstructural and mechanical properties. The micro hardness value and tensile strength at weldment is higher than base material. The mathematical model for predicting hardness and tensile value was generated and validated. The validation fell within 90% prediction interval. The optimize parameters were generated in maximizing hardness and tensile value.